2014
DOI: 10.5435/jaaos-22-10-643
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Langerhans Cell Histiocytosis

Abstract: Langerhans cell histiocytosis is a rare group of disorders without a well-understood etiology. Known formerly as histiocytosis X, the disease has a wide spectrum of clinical presentations, including eosinophilic granuloma (solitary bone lesion), diabetes insipidus, and exophthalmos. It is also known by several eponyms, including Hand-Schüller-Christian disease when it manifests as a triad of cranial bone lesions and Letterer-Siwe disease when it is found in infantile patients with severely disseminated disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 27 publications
1
61
0
2
Order By: Relevance
“…The rate peak is among children aged 5 to 15 (8). LCH is more common in males compared to females (9).…”
Section: Discussionmentioning
confidence: 99%
“…The rate peak is among children aged 5 to 15 (8). LCH is more common in males compared to females (9).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a tissue biopsy for histopathologic examination is required to diagnose EG formally. For patients with unifocal osseous lesions, the overall benefits of needle or open biopsy remains controversial [1]. In our practice, for pediatric cervical EG patients suffered from neurological deficits and/or had SINS ≥7, we suggested surgery as an emergent treatment choice to prevent these children from any possible impending disastrous damages.…”
Section: Discussionmentioning
confidence: 99%
“…Although thoracic segments is the most preferential spine localization in EG patients of all ages with vertebral involvement [1, 2], data of previous studies and our research has suggested that incidence in the cervical spine is the highest in pediatric patients with spinal EG [3, 4]. …”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations